Preparation method and application of silicon-based functionalized fluorene-based polysubstituted acetylene copolymer and gas separation membrane of silicon-based functionalized fluorene-based polysubstituted acetylene copolymer

By preparing silicon-based functionalized fluorene-based polysubstituted acetylene copolymers and combining them with desilication treatment, the balance between permeability and selectivity in polymer gas separation membrane materials was solved, resulting in a gas separation membrane with high permeability and good thermal stability, suitable for the separation of gases such as CO2, O2, and N2.

CN121005828APending Publication Date: 2025-11-25LISHUI UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510961359.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-14
Publication Date
2025-11-25

AI Technical Summary

Technical Problem

Existing polymer gas separation membrane materials struggle to achieve a balance between permeability and selectivity. Traditional polymer membrane materials are prone to structural collapse after desilication treatment, which affects gas transport performance.

Method used

By preparing silicon-functionalized fluorene-based multisubstituted acetylene copolymers, the steric hindrance effect of silicon is used to regulate polymer chain stacking, forming a loose porous structure. The pore structure is then optimized through desilication treatment. Combined with the thermal stability of the rigid fluorene framework, a gas separation membrane with high gas permeability and good thermal stability is prepared.

Benefits of technology

It achieves a balance between high gas permeability and selectivity, with CO2 permeability up to 36,900 Barrer, O2 permeability up to 19,800 Barrer, O2/N2 selectivity of 1.2-1.9, and thermal decomposition temperature exceeding 420℃. It is suitable for the separation of gases such as CO2, O2, and N2 and has industrialization potential.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121005828A_ABST
    Figure CN121005828A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of a silicon-based functionalized fluorenyl polysubstituted acetylene copolymer and a gas separation membrane thereof. Belongs to the technical field of polymer material and gas separation. The invention provides a new thought for preparation of a high-permeability gas separation membrane material. The preparation method comprises the following steps: carrying out copolymerization on 1-phenyl-2-(7-trimethylsilyl-9, 9-bis (trimethylsilyl-fluorene-2-yl) acetylene and 1-phenyl-2-(7-trimethylsilyl-9, 9-dimethyl-fluorene-2-yl) acetylene under the catalysis of TaCl5-n-Bu4Sn, so as to prepare a copolymer with high molecular weight; the preparation method comprises the following steps of: carrying out film casting on a solution of the nano-silver oxide, and then carrying out desiliconization treatment by using normal hexane / trifluoroacetic acid to obtain a gas separation membrane with the thickness of 100-220 microns, the specific surface area of 298-492 m / g and the total pore volume of 0.134-0.299 cm / g. The prepared separation membrane has the advantages that the COpermeability is up to 36,900 Barrer, the Opermeability is 19,800 Barrer, the thermal decomposition temperature exceeds 420 DEG C, the separation membrane can be used for separating gases such as COO, ON and the like, the preparation process is simple and convenient, and the industrial potential is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of polymer materials and gas separation technology, specifically relating to a method for synthesizing a silicon-based functionalized fluorene-based multisubstituted acetylene copolymer, a process for preparing a gas separation membrane based on the copolymer, and its application in the separation of gases such as CO2, O2, and N2. Background Technology

[0002] Gas separation membrane technology has key applications in energy, chemical engineering, and environmental governance, such as natural gas purification, industrial waste gas treatment, and medical oxygen production. Currently, the development of high-performance gas separation membrane materials faces a core challenge: the permeability-selectivity trade-off. Traditional polymer membranes (such as polyimide and polysulfone), due to their tightly packed molecular chains, offer excellent selectivity but low gas permeability. High-performance gas separation membranes need to simultaneously possess high gas permeability and good selectivity, but traditional polymer membrane materials are often limited by the "permeability-selectivity trade-off" effect, making it difficult to meet industrial demands. While high free volume polymers (such as trimethylsilyl polyacetylene) can improve permeability by introducing large side groups, they often suffer from decreased selectivity and physical aging problems due to weak inter-chain interactions. Developing novel polymer materials with unique molecular structures and high free volume is crucial to overcoming this bottleneck.

[0003] Multisubstituted acetylene polymers, due to their rigid backbone and tunable side-chain structures, have become a research hotspot for overcoming traditional trade-offs. The research focus of silicon-based polymer membranes lies in controlling the microporous structure of the membrane through silicon-based functional groups. The introduction of trimethylsilyl (SiMe3) can increase the polymer chain spacing through steric hindrance, forming interconnected gas transport channels; however, the insufficient thermal stability of silicon remains a problem. Fluorene-based polymers, due to their rigid fluorene ring structure, possess excellent thermal stability and mechanical strength, and their π-π stacking characteristics can control the molecular chain arrangement, exhibiting unique advantages in gas separation. However, the porosity of pure fluorene-based polymers is limited. How to combine the rigid framework of fluorene with the porosity control capabilities of silicon to develop novel polymer materials with unique molecular structures and high free volume has become the key to overcoming the performance bottlenecks of traditional membrane materials.

[0004] Desilication technology has gradually attracted attention in the modification of membrane materials. This method removes silicon groups through chemical means, which can induce the formation of micropores inside the polymer and optimize pore connectivity. However, in existing studies, the desilication process is often accompanied by polymer chain collapse, leading to a decrease in permeability. How to precisely control the desilication conditions to balance pore structure and chain rigidity remains a technical challenge that urgently needs to be solved. Summary of the Invention

[0005] Existing research indicates that multisubstituted acetylene polymers, due to their rigid backbone and tunable side-chain structure, show potential in gas separation. However, how to further optimize the polymer chain stacking structure and control the free volume through molecular design to simultaneously improve gas permeability and selectivity remains a pressing issue. Furthermore, traditional silicon-containing polymers are prone to structural collapse after desilication, affecting gas transport performance. Therefore, a novel strategy is needed to both control the pore structure through desilication and maintain material stability.

[0006] This invention aims to provide a method for preparing a silicon-based functionalized fluorene-based multisubstituted acetylene copolymer. By controlling the pore structure of the material through molecular structure design and desilication treatment, a gas separation membrane with high gas permeability and good thermal stability can be prepared.

[0007] One objective of this invention is to provide a method for preparing a silicon-based functionalized fluorene-based multisubstituted acetylene copolymer, comprising the following steps: Step 1: Synthesize 1-phenyl-2-(7-trimethylsilyl-9,9-bistrimethylsilyl-fluoren-2-yl)acetylene monomer; Step 2: Synthesize 1-phenyl-2-(7-trimethylsilyl-9,9-dimethylfluorene-2-yl)acetylene monomer; Step 3: Under a dry nitrogen atmosphere, 1-phenyl-2-(7-trimethylsilyl-9,9-bistrimethylsilyl-fluorene-2-yl)acetylene and 1-phenyl-2-(7-trimethylsilyl-9,9-dimethyl-fluorene-2-yl)acetylene were dissolved in cyclohexane, and TaCl5 and tetrabutyltin (n-Bu4Sn) were added. The mixture was reacted at 80°C for 24 h, precipitated with methanol, filtered, and dried under vacuum to obtain the copolymer.

[0008] Further specifying the steps, in step 1, the synthesis of 1-phenyl-2-(7-trimethylsilyl-9,9-bis(trimethylsilyl-fluorene-2-yl)acetylene monomer is as follows: Under nitrogen protection, 2,7-dibromo-9,9-bis(trimethylsilyl)fluorene is dissolved in diethyl ether, and a solution of n-butyllithium is slowly added dropwise at 0°C. After the addition is complete, the mixture is stirred at room temperature for 1 h. Trimethylchlorosilane is added and stirred at room temperature for 24 h. After extraction, drying, and purification by column chromatography, 2-bromo-7-trimethylsilyl-9,9-bis(trimethylsilyl)fluorene is obtained. The brominated product, phenylacetylene, bis(triphenylphosphine)palladium dichloride, cuprous iodide, and triphenylphosphine are dissolved in triethylamine, stirred at 80°C for 24 h, extracted, dried, and purified by column chromatography to obtain the desired monomer.

[0009] Further specifying step 2, the synthesis of 1-phenyl-2-(7-trimethylsilyl-9,9-dimethylfluorene-2-yl)acetylene monomer involves using fluorene as a starting material. Iodomethane, potassium iodide, potassium hydroxide, and DMSO are added, and the mixture is reacted at room temperature for 24 h to generate 9,9-dimethylfluorene. This 9,9-dimethylfluorene is dissolved in diethyl ether, and a solution of n-butyllithium is slowly added dropwise at 0°C. After the addition is complete, the mixture is stirred at room temperature for 1 h. Trimethylchlorosilane is then added, and the mixture is stirred at room temperature for 24 h. The mixture is extracted, dried, and purified by column chromatography to obtain 2-bromo-7-trimethylsilyl-9,9-dimethylfluorene. The brominated product, phenylacetylene, bis(triphenylphosphine)palladium dichloride, cuprous iodide, and triphenylphosphine are dissolved in triethylamine, stirred at 80°C for 24 h, extracted, dried, and purified by column chromatography to obtain the desired monomer.

[0010] Further specifying, in step 3, the molar ratio of 1-phenyl-2-(7-trimethylsilyl-9,9-bistrimethylsilyl-fluoren-2-yl)acetylene to 1-phenyl-2-(7-trimethylsilyl-9,9-dimethyl-fluoren-2-yl)acetylene is 4:1 to 1:4.

[0011] Further specifying, in step 1, the concentration of TaCl5 is 0.02M.

[0012] Further specifying, in step 1, the concentration of tetrabutyltin (n-Bu4Sn) is 0.04M.

[0013] Another objective of this invention is to provide a method for preparing a gas separation membrane, comprising the following steps: dissolving the copolymer prepared by any of the above methods in toluene, casting it into a membrane, peeling off the membrane after the solvent evaporates, soaking it in methanol for 24 h and then drying it; then immersing it in a hexane-trifluoroacetic acid mixture for desilication treatment, washing it with triethylamine / hexane, soaking it in methanol, and drying it to obtain a gas separation membrane.

[0014] Further specifying, the thickness of the membrane is 100μm-220μm.

[0015] Further specified, the copolymer was dissolved in toluene at a concentration of 2.5 wt%.

[0016] Further specified, in the hexane-trifluoroacetic acid mixture, the volume ratio of hexane to trifluoroacetic acid is 1:1, and the desilication treatment time is 48h.

[0017] Further specifying, the volume ratio of triethylamine to n-hexane is 1:1.

[0018] This invention relates to a copolymer of 1-phenyl-2-(7-trimethylsilyl-9,9-bistrimethylsilyl-fluoren-2-yl)acetylene (Flu1) and 1-phenyl-2-(7-trimethylsilyl-9,9-dimethyl-fluoren-2-yl)acetylene (Flu2) under TaCl5-n-Bu4Sn catalysis, yielding copolymers with molecular weights ranging from 629,000 to 1,810,000. After solution casting into a film, the film is desilication treated with hexane / trifluoroacetic acid to obtain a gas separation membrane with a thickness of 100-220 μm, a specific surface area of ​​298-492 m² / g, and a total pore volume of 0.134-0.299 cm³ / g. This membrane exhibits a CO2 permeability of up to 36,900 Barrer, an O2 permeability of 19,800 Barrer, an O2 / N2 selectivity of 1.2-1.9, and a thermal decomposition temperature exceeding 420℃. It can be used for the separation of gases such as CO2, O2, and N2. The preparation process is simple and has industrialization potential.

[0019] The beneficial effects of this invention are: This invention introduces silicon-functionalized fluorene side chains and utilizes the steric hindrance effect of silicon to regulate polymer chain stacking, forming a loose porous structure that gives the copolymer membrane excellent gas permeability. Specifically, the Copoly(Flu1-Flu2) (4:1) membrane achieves a CO2 permeability of 36,900 Barrer and an O2 permeability of 19,800 Barrer, significantly higher than traditional polymer membranes.

[0020] After the desilication treatment of this invention, the pore structure of the membrane is further optimized, and the permeability of some membranes is improved. For example, the CO2 permeability of the DScopoly(Flu1-Flu2) (2:1) membrane can reach 36,600 Barrer, while maintaining good selectivity.

[0021] The separation membrane of this invention has excellent thermal stability, with a thermal decomposition initiation temperature higher than 420°C, making it suitable for high-temperature gas separation scenarios.

[0022] The preparation process of this invention is simple, and the membrane structure and performance can be precisely controlled by adjusting the monomer ratio and desilication treatment conditions, which has good prospects for industrial application. Attached Figure Description

[0023] Figure 1 This is a schematic diagram of the copolymer synthesis route; Figure 2 The FT-IR spectra of Copoly(Flu1-Flu2)(1:4) and DScopoly(Flu1-Flu2)(1:4) show the changes in silicon-based characteristic peaks before and after desilication. Figure 3 The TGA curves of the copolymer film and the desilicified film indicate the thermal stability of the materials; Figure 4 The XRD patterns of the copolymer film and the desilicified film reflect the changes in chain stacking structure; Figure 5 The N2 adsorption-desorption isotherms for the copolymer film and the desilicified film, and the specific surface area of ​​the reactant material; Figure 6 The pore size distribution of the copolymer membrane and the desilicified membrane reveals the pore structure characteristics; Figure 7 The graph shows the relationship between oxygen permeability and aging time for copolymer membranes and desilicified membranes, illustrating the anti-aging properties of the materials. Detailed Implementation

[0024] Example 1: The preparation method of the silicon-functionalized fluorene-based polysubstituted acetylene copolymer in this example is carried out according to the following steps: Step 1. Synthesis of Flu1: Under nitrogen protection, 35.0 g (75 mmol) of 2,7-dibromo-9,9-bistrimethylsilylfluorene was dissolved in anhydrous diethyl ether (100 mL), and the solution was cooled to 0°C in an ice bath. A hexane solution of n-butyllithium (n-BuLi) (28.7 mL, 2.6 M, 75 mmol) was slowly added dropwise, and the solution was stirred at room temperature for 1 h after the addition was complete. The solution was then cooled back to 0°C, and a diethyl ether solution of 8.1 g (75 mmol) of trimethylchlorosilane (50 mL) was added dropwise, and the solution was stirred at room temperature for 24 h. The solution was quenched with a small amount of water, extracted with diethyl ether, washed with water, dried over anhydrous sodium sulfate, concentrated, and then subjected to silica gel column chromatography (eluent: n-hexane) to give 2-bromo-7-trimethylsilyl-9,9-bistrimethylsilylfluorene (white solid, yield 89%). Under nitrogen protection, the above-mentioned brominated product, phenylacetylene (4.83 g, 47 mmol), bis(triphenylphosphine)palladium dichloride (PdCl2(PPh3)2) (0.133 g, 0.19 mmol), cuprous iodide (CuI) (0.216 g, 1.14 mmol), and triphenylphosphine (PPh3) (0.198 g, 0.76 mmol) were dissolved in triethylamine (300 mL). The mixture was stirred at 80 °C for 24 h, the triethylamine was removed by evaporation, the product was dissolved in diethyl ether, washed with hydrochloric acid (1 M) and water, and dried over anhydrous sodium sulfate. After concentration, the product was subjected to silica gel column chromatography (eluent: n-hexane) to give 1-phenyl-2-(7-trimethylsilyl-9,9-bistrimethylsilyl-fluorene-2-yl)acetylene (Flu1) monomer (white solid, 70% yield).

[0025] Step 2. Synthesis of Flu2: Using fluorene as a starting material, iodomethane, potassium iodide, potassium hydroxide, and DMSO were added and reacted at room temperature for 24 h to generate 9,9-dimethylfluorene. Following Step 1 of Flu1, 2,7-dibromo-9,9-dimethylfluorene was replaced with the starting material and reacted with n-BuLi at 0 °C for 1 h, followed by reaction with trimethylchlorosilane at room temperature for 24 h to obtain 2-bromo-7-trimethylsilyl-9,9-dimethylfluorene. The above brominated product was coupled with phenylacetylene (under the same conditions as Flu1) to obtain 1-phenyl-2-(7-trimethylsilyl-9,9-dimethyl-fluorene-2-yl)acetylene (Flu2) monomer (white solid, yield 75%).

[0026] Step 3. Copolymer synthesis: Synthesis of Copoly(Flu1-Flu2) copolymer (taking Copoly(Flu1-Flu2) (4:1) as an example): Under a dry nitrogen atmosphere, Flu1 (0.48 g) and Flu2 (0.37 g) were dissolved in 5.0 mL of cyclohexane to prepare a monomer solution; separately, TaCl5 (0.14 g) and n-Bu4Sn (0.8 M cyclohexane solution, 1.0 mL) were dissolved in 4.0 mL of cyclohexane to prepare a catalytic solution.

[0027] The monomer solution was added to the catalytic solution and reacted at 80°C for 24 h. After the reaction was complete, methanol was added to quench the catalyst, the product was dissolved in toluene, and then poured into a large amount of methanol to precipitate the product. The precipitate was filtered and dried under vacuum to obtain the copolymer with a yield of 64%, a molecular weight of Mw = 629,000, and a PDI of 1.31. The molecular weight results of the copolymer with different feed ratios are shown in Table 1.

[0028] Table 1 Preparation of the separation membrane in this embodiment: The copolymer was dissolved in toluene to prepare a 2.5 wt% solution, which was then cast into a membrane. After solvent evaporation, a Copoly(Flu1-Flu2) membrane was obtained. The membrane was immersed in a hexane / trifluoroacetic acid (v / v 1:1) mixture for 48 h for desilication treatment, resulting in a DScopoly(Flu1-Flu2) membrane. The membrane was washed with triethylamine / hexane (1:1), soaked in methanol for 24 h, and then air-dried.

[0029] Performance testing 1. Gas Permeability Test: The gas permeability of the membrane was tested using a differential pressure gas permeameter at 25℃, upstream pressure 1 atm, and downstream pressure 3 Pa. The results are shown in Table 2. With the increase of Flu2 ratio (4:1 → 1:4), CO2 permeability decreased (36,900 → 19,600 Barrer), but O2 / N2 selectivity increased (1.3 → 1.8). Specifically, the Copoly(Flu1-Flu2) (4:1) membrane had a CO2 permeability of 36,900 Barrer, an O2 permeability of 19,800 Barrer, and an N2 permeability of 15,500 Barrer, with an O2 / N2 selectivity of 1.3. The desilication-treated DScopoly(Flu1-Flu2) (4:1) membrane had a CO2 permeability of 26,600 Barrer, an O2 permeability of 9,000 Barrer, and an N2 permeability of 5,000 Barrer.

[0030] Table 2 2. Thermal stability test: TGA analysis showed that neither Copoly(Flu1-Flu2) membrane nor DScopoly(Flu1-Flu2) membrane showed significant weight loss below 420℃, demonstrating excellent thermal stability.

[0031] Example 2: Copolymer films with different monomer ratios By varying the feed ratio of Flu1 to Flu2, copolymer membranes with compositions of 2:1, 1:1, 1:2, and 1:4 were prepared, and their gas permeability was tested. The results showed that when Flu1:Flu2 = 1:4, the copolymer membrane had the highest molecular weight (Mw = 1,810,000), but the permeability decreased with increasing Flu2 content, demonstrating the regulatory effect of monomer ratio on the material's structure and properties.

[0032] Comparative Example 1: Performance Comparison of Un-Desilication and Desilication Films Comparing the performance of Copoly(Flu1-Flu2)(2:1) membrane and DScopoly(Flu1-Flu2)(2:1) membrane, it was found that the membrane density decreased after desilication (0.793 g / cm³ → 0.757 g / cm³), and the CO2 permeability increased from 29,700 Barrer to 36,600 Barrer. This indicates that desilication treatment can effectively regulate the pore structure of the membrane and improve gas transport performance.

[0033] The following experiments were used to verify the effectiveness of the invention: 1. Material preparation 1-Phenyl-2-(7-trimethylsilyl-9,9-bistrimethylsilylfluoren-2-yl)acetylene (Flu1) and 1-phenyl-2-(7-trimethylsilyl-9,9-dimethylfluoren-2-yl)acetylene (Flu2) monomers were synthesized and copolymerized using TaCl5-n-Bu4Sn catalyst. A series of copolymers were prepared by adjusting the feed ratio of Flu1 to Flu2 (4:1 to 1:4).

[0034] Typical synthesis steps: Under nitrogen protection, Flu1 (0.48 g) and Flu2 (0.37 g) were dissolved in cyclohexane (5.0 mL), and reacted with a catalytic solution of TaCl5 (0.14 g) and n-Bu4Sn (1.0 mL) at 80 °C for 24 h. After precipitation with methanol and vacuum drying, the copolymer was obtained with a yield of 64%-76%.

[0035] Membrane preparation and desilication Copolymer membranes with a thickness of 100-220 μm were prepared by solution casting. A 2.5 wt% copolymer toluene solution was poured into a petri dish. After the solvent evaporated, the membrane was peeled off, soaked in methanol for 24 h, and then dried.

[0036] Desilication treatment: The membrane was immersed in a mixture of n-hexane and trifluoroacetic acid (v / v1:1) for 48 h, washed with triethylamine / n-hexane, soaked in methanol, and then dried to obtain a desilication membrane (DScopoly(Flu1-Flu2)).

[0037] Copolymerization and Membrane Structure Regulation As the Flu2 content increased (Flu1:Flu2 from 4:1 to 1:4), the molecular weight of the copolymer increased from 629,000 to 1,810,000, which is attributed to the smaller steric hindrance of the 9,9-dimethylfluorenyl group in Flu2, which is conducive to chain growth.

[0038] Gas permeation mechanism The steric hindrance effect of the silicon group in the copolymer creates a high free volume, while the rigid skeleton of the fluorene group maintains channel stability. The low density (0.790 g / cm³) and high free volume fraction of Copoly (Flu1-Flu2) (4:1) work synergistically to enable its permeability to exceed that of a single homopolymer.

[0039] The effect of desilicification on permeability is composition-dependent: the permeability of the membrane with high Flu1 content (4:1) decreased after desilicification (CO2 decreased from 36,900 to 26,600 Barrer) due to chain collapse caused by silicon removal; while the permeability of the membrane with high Flu2 content (2:1) increased after desilicification (CO2 increased from 29,700 to 36,600 Barrer), which is attributed to the methyl substituents maintaining pore connectivity.

[0040] Physical aging properties A 240-day aging test showed that the O2 permeability decay rate of the desiliconized membrane (such as DScopoly (Flu1-Flu2)(2:1)) was lower than that of the non-desiliconized membrane, and the anti-aging performance of the low-density (0.757 g / cm³) material was better than that of traditional high free volume polymers.

[0041] By combining the pore control capability of silicon-based membranes with the rigid framework of fluorene-based membranes, a balance between permeability and stability is achieved through copolymerization composition optimization (Flu1:Flu2 = 4:1 to 1:4), breaking through the performance trade-off limitations of traditional membrane materials.

[0042] The TaCl5-n-Bu4Sn catalytic copolymerization reaction is highly efficient (yield ≥64%) and controllable (molecular weight adjustable). The desilication treatment can precisely control the pore structure of the membrane, forming a "desilication-induced micropore" mechanism.

[0043] The CO2 permeability reaches 36,900 Barrer, which is the leading level among similar silicon-based polymer membranes, and the thermal stability (>420℃) meets the requirements for high-temperature operating conditions.

[0044] FT-IR spectra of Copoly(Flu1-Flu2)(1:4) and DScopoly(Flu1-Flu2)(1:4) show the changes in silicon-based characteristic peaks before and after desilication, as follows: Figure 2 As shown, by Figure 2 It can be seen that the original copolymer film exhibits characteristic absorption bands of 1250 cm⁻¹ (Si-CH deformation) and 1120 cm⁻¹ (Si-C stretching), which are attributed to the trimethylsilyl group. After desilication, these peaks completely disappeared in the DScopoly(Flu1-Flu2) (1:4) spectrum, confirming that the SiMe3 group was successfully removed.

[0045] The TGA curves of the copolymer film and the desilication film indicate the thermal stability of the materials, such as... Figure 3 As shown, by Figure 3 As can be seen, both Copoly(Flu1-Flu2) and DScopoly(Flu1-Flu2) membranes exhibit excellent thermal stability, with minimal weight loss observed below 420°C. This performance is comparable to other fluorene-containing polymers reported in the literature, highlighting the robustness of their backbone structure. Notably, the desilication process did not compromise the thermal stability of the membranes, as DScopoly(Flu1-Flu2) maintained a high decomposition onset temperature similar to that of the original copolymer. Due to their rigid backbone and strong intermolecular interactions, these materials possess excellent heat resistance, emphasizing their suitability for high-temperature gas separation applications.

[0046] The XRD patterns of copolymer films and desilication films reflect changes in chain stacking structure, such as... Figure 4 As shown, by Figure 4 It is evident that all films exhibit broad amorphous peaks, indicating a lack of long-range crystalline order. Copoly(Flu1-Flu2) (4:1) shows two prominent peaks at 5.8° (d-spacing = 15.2 Å) and 16.3° (d-spacing = 5.4 Å), corresponding to the interchain packing distance and π-π packing of the aromatic rings, respectively. The unusually large d-spacing (15.2 Å) suggests that the large SiMe3 groups in Flu1 cause loose chain packing. In contrast, Copoly(Flu1-Flu2) (1:4) shows peaks at 6.4° (d-spacing = 13.8 Å) and 15.2° (d-spacing = 5.8 Å), reflecting a slight increase in packing density with increasing Flu2 proportion. Following desiliconization, DScopoly(Flu1-Flu2) (4:1) showed a significant shift of the small angular peak to 8.4° (d-spacing = 10.5 Å), indicating a tighter chain packing due to the removal of the bulky SiMe3 group. However, DScopoly(Flu1-Flu2) (1:4) retained a relatively large d-spacing of 13.4 Å (2θ1 = 6.6°), likely due to the residual steric hindrance of the methyl group in the Flu2 unit. These results highlight the crucial role of chemical structure in regulating chain packing and free volume, which directly affects gas transport properties.

[0047] N2 adsorption-desorption isotherms of copolymer films and desiliconized films, and the specific surface area of ​​the reacting materials, as shown in the figure. Figure 5 As shown, by Figure 5 It can be seen that Copoly(Flu1-Flu2)(1:4) exhibits the highest BET surface area (492 m²). 2 / g) and total pore volume (0.299 cm³) 3 / g), which is due to its loose chain-like stacking and the presence of large SiMe3 groups, resulting in abundant porosity. With increasing Flu2 content, the specific surface area and total pore volume of BET decrease (e.g., the specific surface area of ​​Copoly(Flu1-Flu2) (1:4) is 298 m²). 2 / g, total pore volume is 0.134 cm³ 3 / g), consistent with the dense packing observed by XRD. The effect of desilication on the pore structure, however, is quite different. DScopoly(Flu1-Flu2) (4:1) shows a reduction in BET surface area to 450 m². 2 / g, but retains a high total pore volume (0.238 cm³).3 The figure ( / g) indicates that desilication reduces microporosity while inducing the formation of larger pores. In contrast, the BET surface area of ​​DScopoly(Flu1-Flu2) (1:4) is 453 m² / g, indicating that desilication reduces microporosity while inducing the formation of larger pores. 2 / g) and total pore volume (0.261 cm³) 3 The increase in both ( / g) indicates that the removal of the SiMe3 group created additional free volume in the steric hindrance of the methyl group in the Flu2 unit.

[0048] The pore size distribution of the copolymer membrane and the desilication membrane reveals pore structure characteristics such as... Figure 6 As shown, by Figure 6 It can be seen that the pore size distribution of all membranes is in the range of 3-20 nm. With the increase of Flu1 unit content, the pore size and total pore volume of Copoly(Flu1-Flu2) increase. This also indicates that Flu1 units can hinder chain stacking. In addition, the pore size distribution of DScopoly(Flu1-Flu2) (1:4) membranes is slightly shifted towards macropores, which is consistent with the increase of BET surface area and total pore volume.

[0049] The relationship between oxygen permeability and aging time for copolymer membranes and desilicified membranes is shown in the figure. Figure 7 As shown, Copoly(Flu1-Flu2) and DScopoly(Flu1-Flu2) exhibit excellent anti-aging properties, with permeability loss of less than 10% within 240 days. This behavior is attributed to their rigid framework, tailored free volume, and the synergistic effect of copolymerization and desilication.

Claims

1. A method for preparing a silicon-based functionalized fluorene-based polysubstituted acetylene copolymer, characterized in that, Includes the following steps: Step 1: Synthesize 1-phenyl-2-(7-trimethylsilyl-9,9-bistrimethylsilyl-fluoren-2-yl)acetylene monomer; Step 2: Synthesize 1-phenyl-2-(7-trimethylsilyl-9,9-dimethylfluorene-2-yl)acetylene monomer; Step 3: Under a dry nitrogen atmosphere, 1-phenyl-2-(7-trimethylsilyl-9,9-bistrimethylsilyl-fluorene-2-yl)acetylene and 1-phenyl-2-(7-trimethylsilyl-9,9-dimethyl-fluorene-2-yl)acetylene were dissolved in cyclohexane, and TaCl5 and tetrabutyltin (n-Bu4Sn) were added. The mixture was reacted at 80°C for 24 h, precipitated with methanol, filtered, and dried under vacuum to obtain the copolymer.

2. The method according to claim 1, characterized in that, Synthesis of 1-phenyl-2-(7-trimethylsilyl-9,9-bistrimethylsilyl-fluorene-2-yl)acetylene monomer: Under nitrogen protection, 2,7-dibromo-9,9-bistrimethylsilylfluorene was dissolved in diethyl ether, and n-butyllithium solution was slowly added dropwise at 0°C. After the addition was complete, the mixture was stirred at room temperature for 1 h. Trimethylchlorosilane was added and stirred at room temperature for 24 h. After extraction, drying, and purification by column chromatography, 2-bromo-7-trimethylsilyl-9,9-bistrimethylsilylfluorene was obtained. The brominated product, phenylacetylene, bis(triphenylphosphine)palladium dichloride, cuprous iodide, and triphenylphosphine were dissolved in triethylamine, stirred at 80°C for 24 h, extracted, dried, and purified by column chromatography to obtain the desired monomer.

3. The method according to claim 1, characterized in that, 1-Phenyl-2-(7-trimethylsilyl-9,9-dimethylfluorene-2-yl)acetylene monomer was synthesized by adding fluorene as a raw material, iodomethane, potassium iodide, potassium hydroxide, and DMSO, and reacting at room temperature for 24 h to generate 9,9-dimethylfluorene. 9,9-Dimethylfluorene was dissolved in diethyl ether, and n-butyllithium solution was slowly added dropwise at 0 °C. After the addition was complete, the mixture was stirred at room temperature for 1 h. Trimethylchlorosilane was then added and stirred at room temperature for 24 h. The mixture was extracted, dried, and purified by column chromatography to obtain 2-bromo-7-trimethylsilyl-9,9-dimethylfluorene. The brominated product, phenylacetylene, bis(triphenylphosphine)palladium dichloride, cuprous iodide, and triphenylphosphine were dissolved in triethylamine, stirred at 80 °C for 24 h, extracted, dried, and purified by column chromatography to obtain the desired monomer.

4. The method according to claim 1, characterized in that, The molar ratio of 1-phenyl-2-(7-trimethylsilyl-9,9-bistrimethylsilyl-fluoren-2-yl)acetylene to 1-phenyl-2-(7-trimethylsilyl-9,9-dimethyl-fluoren-2-yl)acetylene was 4:1 to 1:4, the concentration of TaCl5 was 0.02 M, and the concentration of tetrabutyltin (n-Bu4Sn) was 0.04 M.

5. A method for preparing a gas separation membrane, characterized in that, Includes the following steps: The copolymer prepared by any one of claims 1-4 is dissolved in toluene, cast into a film, and after the solvent evaporates, the film is peeled off, soaked in methanol for 24 h and then dried; then it is immersed in a hexane-trifluoroacetic acid mixture for desilication treatment, washed with triethylamine / hexane, soaked in methanol, and dried to obtain a gas separation membrane.

6. The method according to claim 5, characterized in that, The thickness of the membrane is 100 μm-220 μm.

7. The method according to claim 5, characterized in that, The copolymer was dissolved in toluene at a concentration of 2.5 wt%.

8. The method according to claim 5, characterized in that, In the hexane-trifluoroacetic acid mixture, the volume ratio of hexane to trifluoroacetic acid was 1:1, and the desilication treatment time was 48 h.

9. The method according to claim 5, characterized in that, The volume ratio of triethylamine to n-hexane is 1:

1.

10. The application of a gas separation membrane prepared by the method according to any one of claims 5-9 in the separation of CO2, O2, and N2 gases.